Fourier Transform Infrared Spectroscopy - Useful Analytical Tool for Non-Destructive Analysis - Litescu, Simona-Carmen; Teodor, Eugenia D.; Truica, Georgiana-Ileana; Tache, Andreia; Radu, Gabriel-Lucian (IntechOpen, 2012)
None